A novel cell-based screen identifies chemical entities that reverse the immune-escape phenotype of metastatic tumours - Nohara, Lilian L.; Ellis, Samantha L. S.; Dreier, Carola; Dada, Sarah; Saranchova, Iryna; Choi, Kyong Bok; Munro, Lonna; Pfeifer, Cheryl G.; Al Haddad, Eliana; Coyle, Krysta M.; Morrice, Jessica R.; Shim, Daniel Joo Sung; et al. (Frontiers in Pharmacology, 2023)
Genetic and epigenetic events have been implicated in the downregulation of the cellular antigen processing machinery (APM), which in turn, has been associated with cancer evasion of the immune system. When these essential components are lacking, cancers develop the ability to subvert host immune surveillance allowing cancer cells to become invisible to the immune system and in turn promote cancer metastasis. Here, we describe and validate the first novel high-throughput cell-based assay to identify chemical extracts and unique chemical entities that reverse the downregulation APM components in metastatic tumours. (+)-Curcuphenol, a common sesquiterpene phenol derived from turmeric, was identified from marine invertebrate extracts using the cell-based screen that induces the expression of the APM components, TAP-1 and MHC-I molecules, thereby reversing the immune escape deficiency in metastatic prostate and lung carcinomas. Turmeric and curcumins that contain curcuphenol have long been utilized not only as a spice in the preparation of food, but also in traditional medicines for treating cancers. The remarkable discovery that a common component of spices can increase the expression of APM components and MHC-I metastatic tumours and therefore reverse immune-escape mechanisms provides a rationale for the development of foods and advanced nutraceuticals as therapeutic candidates for harnessing the power of the immune system to recognize and destroy metastatic cancers.